2021
DOI: 10.31665/jfb.2021.15281
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds in cereal grains and effects of processing on their composition and bioactivities: a review

Abstract: Cereals are a staple food in the diets of many populations globally. Besides their nutritive function in food, they are also rich in various groups of bioactive compounds, especially polyphenols. Wheat, rice, barley, rye, oat, maize, millet, sorghum, and other cereal grains present a great variety of phenolic acids, flavonoids, proanthocyanidins, alkylresorcinols, and lignans, which can be affected in many ways by the post-harvest treatments and further processing of these feedstocks. This review discusses up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…The storage time have shown to decrease the phenolic concentrations in sorghum grain and flour ( 61 ). Other factors related to the cultivation and harvesting practices also influence the phenolic contents in cereal grains and might also explain observed differences ( 62 ). The TPC range obtained in this study was comparable to that reported by De la Parra et al ( 63 ) (243.8–320.1 mg GAE/100 g DW, samples from the United States) and higher than results found in maize landraces with variable pigmentations from Chile (132.2–262.5 mg GAE/100 g DW) ( 47 ), Mexico (77.3–123.6 mg GAE/100 g DW) ( 64 ) and India (102.3–206.4 mg GAE/100 g DW) ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…The storage time have shown to decrease the phenolic concentrations in sorghum grain and flour ( 61 ). Other factors related to the cultivation and harvesting practices also influence the phenolic contents in cereal grains and might also explain observed differences ( 62 ). The TPC range obtained in this study was comparable to that reported by De la Parra et al ( 63 ) (243.8–320.1 mg GAE/100 g DW, samples from the United States) and higher than results found in maize landraces with variable pigmentations from Chile (132.2–262.5 mg GAE/100 g DW) ( 47 ), Mexico (77.3–123.6 mg GAE/100 g DW) ( 64 ) and India (102.3–206.4 mg GAE/100 g DW) ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…Foxtail millet is another rich source of phenolics [ 50 , 51 ] and moderate amounts of flavonoids [ 51 ], bioactive peptides, carotenoids, and tocols. The major phenolic acids are ferulic acid, vanillic acid, and soluble forms of caffeic and sinapic acids [ 53 ]. Zeaxanthin and lutein are the most common carotenoids in foxtail.…”
Section: An Overview Of Bioactive Compounds Of Milletsmentioning
confidence: 99%
“…Phenolic compounds are secondary plant metabolites and their basic structures consist of a benzene ring to which one or more hydroxyl groups are attached. Depending on their structural features, phenolics can be broken down into several subgroups, including phenolic acids, flavonoids, tannins (hydrolysable and condensed), stilbenoids, lignans, coumarins, and tyrosol (Shahidi et al, 2021).…”
Section: Bioactive Compounds From Fruits and Their Health-promoting E...mentioning
confidence: 99%
“…In food matrices, phenolics may exist in the soluble (free or esterified/etherified to fatty acids, carbohydrates, and soluble proteins) and insoluble-bound forms (covalently bound to cell wall molecules, such as fiber, cellulose, and structural protein) (Shahidi et al, 2021;Schefer et al, 2021). Flavonoids, the main phenolic class, are present in high amounts in fruits (Pan et al, 2009); their seeds may possess flavonoid glycosides (attached to a sugar molecule) or aglycones (Fang et al, 2005).…”
Section: Bioactive Compounds From Fruits and Their Health-promoting E...mentioning
confidence: 99%
See 1 more Smart Citation